Todorov and us. Symbols of the other - Marconi, Valerio (Itinerari, 2023)
The present paper assesses some aspects of Todorov’s contribution to Structuralism. His views on alterity and symbolism are relevant to several topics: a) the link between the Conquest of America and the genesis of Capitalism, b) the universalism–relativism antinomy, c) a critical approach to the idea of primitive thought and language. Todorov widens the Structuralist theoretical framework by applying it to historical and moral questions so that his insights can shed light on debates in political philosophy. Todorov’s theory and practice of ethnology is an outstanding example of the unique way in which he combines Structuralist reasoning with the humanistic dimension of social sciences.